2018
DOI: 10.1158/1541-7786.mcr-17-0417
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle–Dependent Tumor Engraftment and Migration Are Enabled by Aurora-A

Abstract: Cell-cycle progression and the acquisition of a migratory phenotype are hallmarks of human carcinoma cells that are perceived as independent processes but may be interconnected by molecular pathways that control microtubule nucleation at centrosomes. Here, cell-cycle progression dramatically impacts the engraftment kinetics of 4T1-luciferase2 breast cancer cells in immunocompetent BALB/c or immunocompromised NOD-SCID gamma (NSG) mice. Multiparameter imaging of wound closure assays was used to track cell-cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
4
23
0
Order By: Relevance
“…While full-length HMMR is able to locate to centrosomes and bind to microtubules [16], the naturally occurring splice variant HMMR (-exon 4) localizes to the mitotic spindle during mitosis but shows nuclear localization during interphase [16,19]. Localization to the nucleus is also seen for a phosphorylated form of HMMR at Thr703 [22]. Phosphorylation at Thr703 was identified by phospho-proteomics [23] and, through the use of antibodies specific for phospho-Thr703 HMMR, it was revealed that phospho-Thr703 not only directs the protein to the nucleus but also may assist in the regulation of the Ran-dependent nuclear transport of targeting protein for Xklp2 (TPX2) [22].…”
Section: Structural Domains In Hmmrmentioning
confidence: 99%
See 2 more Smart Citations
“…While full-length HMMR is able to locate to centrosomes and bind to microtubules [16], the naturally occurring splice variant HMMR (-exon 4) localizes to the mitotic spindle during mitosis but shows nuclear localization during interphase [16,19]. Localization to the nucleus is also seen for a phosphorylated form of HMMR at Thr703 [22]. Phosphorylation at Thr703 was identified by phospho-proteomics [23] and, through the use of antibodies specific for phospho-Thr703 HMMR, it was revealed that phospho-Thr703 not only directs the protein to the nucleus but also may assist in the regulation of the Ran-dependent nuclear transport of targeting protein for Xklp2 (TPX2) [22].…”
Section: Structural Domains In Hmmrmentioning
confidence: 99%
“…Localization to the nucleus is also seen for a phosphorylated form of HMMR at Thr703 [22]. Phosphorylation at Thr703 was identified by phospho-proteomics [23] and, through the use of antibodies specific for phospho-Thr703 HMMR, it was revealed that phospho-Thr703 not only directs the protein to the nucleus but also may assist in the regulation of the Ran-dependent nuclear transport of targeting protein for Xklp2 (TPX2) [22].…”
Section: Structural Domains In Hmmrmentioning
confidence: 99%
See 1 more Smart Citation
“…This inability is related to the effect of temulawak in inducing cell cycles arrest in the G2/M phase. Chu et al, 2018, reported that cellcycle progression and the migratory acquisition are found as independent processes but may be interconnected. The interconnection is through molecular pathways that control microtubule nucleation at centrosomes.…”
Section: Resultsmentioning
confidence: 99%
“…1(a)). FUCCI allows us to study cell motility in G1 separately from cell motility in S/G2/M [6,20,26,27]. Specifically, we investigate cycling cells for differences in motility when the cells are in G1 compared with S/G2/M.…”
Section: Introductionmentioning
confidence: 99%